2011
DOI: 10.1016/j.ajpath.2011.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course and Regional Analyses of the Physiopathological Changes Induced after Cerebral Injection of an Amyloid β Fragment in Rats

Abstract: Alzheimer's disease (AD) is a neurodegenerative pathology characterized by the presence of senile plaques and neurofibrillary tangles, accompanied by synaptic and neuronal loss. The major component of senile plaques is an amyloid ␤ protein (A␤) formed by pathological processing of the A␤ precursor protein. We assessed the time-course and regional effects of a single intracerebroventricular injection of aggregated A␤ fragment 25-35 (A␤ 25-35 ) in rats. Using a combined biochemical, behavioral, and morphological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
129
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(152 citation statements)
references
References 77 publications
10
129
2
Order By: Relevance
“…It has been repeatedly shown that the i.c.v. injection of Ab [25][26][27][28][29][30][31][32][33][34][35] in rats and mice increases b-secretase activity and Ab levels in the hippocampus and cortex of the animals (Klementiev et al, 2007;Chavant et al, 2010;Zussy et al, 2011). All treatments resulted in a significant blockade of Ab 25-35 -induced increase in Ab 1-42 levels measured by ELISA.…”
Section: The Mixed Muscarinic/r1 Ligand Anavex2-73 Prevent Tau Hyperpmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been repeatedly shown that the i.c.v. injection of Ab [25][26][27][28][29][30][31][32][33][34][35] in rats and mice increases b-secretase activity and Ab levels in the hippocampus and cortex of the animals (Klementiev et al, 2007;Chavant et al, 2010;Zussy et al, 2011). All treatments resulted in a significant blockade of Ab 25-35 -induced increase in Ab 1-42 levels measured by ELISA.…”
Section: The Mixed Muscarinic/r1 Ligand Anavex2-73 Prevent Tau Hyperpmentioning
confidence: 99%
“…Moreover, mice overexpressing GSK-3b showed impaired long-term potentiation and memory deficits (Hernandez et al, 2002), which could be attributable to impaired integration of Akt and Wnt signalling onto mammalian target of rapamycin (mTOR) stimulation (Ma et al, 2010(Ma et al, , 2011. Ab peptides also activate directly GSK-3b in vitro and in vivo, although the mechanism remains unclear (Kim et al, 2003;Akiyama et al, 2005;Klementiev et al, 2007;Zussy et al, 2011). Finally, GSK-3b could have a critical role in Ab production (for review, see Cai et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pervious experimental studies have shown that Aβ (25-35) induce a wide pattern of central modifications, reminiscent of the human physiopathology, particularly short-and long-term memory deficit, oxidative stress, apoptosis, neuroinflammation, acetylcholine impairment, hippocampus alteration, tau hyperphosphorylation and amyloid burden (10). The deposition of β-amyloid protein in brain is related to learning impairment and cholinergic neuronal degeneration and the β-amyloid protein-treated rats could be used as AD animal models (11).…”
mentioning
confidence: 99%